GaAs-based photonic integrated circuit platform enabling monolithic ring-resonator-coupled lasers - Jan-Philipp Koester; Hans Wenzel; Jörg Fricke; Matthias Reggentin; Pietro Della Casa; Poojitha Sammeta; Olaf Brox; Michael Ekterai; Mario Kohlbrenner; Andreas Renkewitz; Christof Zink; Thomas Tenzler; et al. (APL Photonics, 2024)
This paper reports on a monolithically integrated gallium arsenide (GaAs)-based photonic integrated circuit platform for wavelengths around 1064 nm. Enabled by spatially selective quantum well removal and two-step epitaxial growth, it supports on-chip gain as well as passive waveguides. In addition, shallow- and deep-etched waveguides are realized. The former result in waveguide losses of less than 2 dB/cm, while the latter enable compact integrated waveguide components. To demonstrate the performance of the platform, racetrack ring resonators based on deep-etched Euler bends and shallow-etched directional couplers are realized, achieving high intrinsic quality factors of 2.6 × 105 and 3.2 × 105 for the fundamental TE and TM mode, respectively. To demonstrate the use of these resonators, ring-resonator-coupled lasers are fabricated, resulting in one-sided output powers of up to 14 mW and single-mode operation with 40 dB side-mode suppression. The successful integration of ring resonators on a GaAs-based active/passive photonic integrated circuit platform paves the way for the realization of fully monolithic, widely tunable, and narrow linewidth ring-resonator-coupled laser sources.